Implementasi Pembelajaran IPA Berbasis Masalah (PBM) di SD Serta Pengaruhnya Terhadap Berpikir Tingkat Tinggi - - Hartati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: The recent teaching problem of natural science in Samarinda is about teachers’ comprehension to problem based learning strategy. They application of problem based learning strategy as learning scenario is very view. The problem can influence the development of elementary school students’ high-level thinking ability in learning natural science. The aim of this research is to describe the influence of problem based learning strategy to the students’ high level thinking ability. The research design was non equivalent control group design. The data colleted was analyzed by anacova. The result of this research was that guided problem strategy increased students’ high level thinking ability.